factorise x^3-6x^2+3x+10 given that (x+1) is a factor.
Answer fast plz.
Answers
Answered by
7
Given f(x) = x^3 - 6x^2 + 3x + 10.
= > x^3 - 7x^2 + x^2 + 10x - 7x + 10
= > (x + 1)(x^2 - 7x + 10)
= > (x + 1)(x^2 - 2x - 5x + 10)
= > (x + 1)(x(x - 2) - 5(x - 2))
= > (x + 1)(x - 2)(x - 5)
Therefore the factors of x^3 - 6x^2 + 3x + 10 = (x + 1)(x - 2)(x - 5).
Hope this helps!
= > x^3 - 7x^2 + x^2 + 10x - 7x + 10
= > (x + 1)(x^2 - 7x + 10)
= > (x + 1)(x^2 - 2x - 5x + 10)
= > (x + 1)(x(x - 2) - 5(x - 2))
= > (x + 1)(x - 2)(x - 5)
Therefore the factors of x^3 - 6x^2 + 3x + 10 = (x + 1)(x - 2)(x - 5).
Hope this helps!
siddhartharao77:
:-)
Answered by
1
Brainlist it if it helps you. please
Attachments:
![](https://hi-static.z-dn.net/files/dc9/7cfcde0b5a44e9adf48bc978a7fba1f6.jpg)
Similar questions
Physics,
8 months ago
History,
8 months ago
Hindi,
1 year ago
French,
1 year ago
Computer Science,
1 year ago